Factors Related to the Delivery Process in the Maternity Room of Bima Hospital - Sri Rahmawati; Rostinah; Megawati (The Indonesian Institute of Science and Technology Research, 2026)
Based on a preliminary study in the Maternity Room of Bima Hospital, data was found from January to May 2025 on the number of maternity patients, namely 218 mothers, consisting of 92 mothers giving birth normally and 126 mothers giving birth by caesarean section (SC). The purpose of the study was to analyze factors related to the Childbirth Process at Bima Hospital. This type of research is quantitative research using secondary data. The sample was 141 people using the Slovin formula with a sampling technique, namely, simple random sampling. Data analysis techniques include univariate analysis and bivariate analysis with the chi-square test. The results of the research obtained were that there was a relationship between the age of the mother and the childbirth process. The results of statistical analysis obtained a value of p (0.019) < 0.05, an odd ratio (OR) value = 2.547, meaning that the age of the mother who is at risk of having the risk of experiencing the SC delivery process 2 times. There was no relationship between maternal parity and the labor process. The results of statistical analysis obtained a value of p (0.000) < 0.05, an odd ratio (OR) value = 1.021, meaning that the parity of women who are at risk of having a risk of experiencing the SC delivery process 1 time. There was no relationship between the gestation of the mother and the labor process. The results of statistical analysis obtained a value of p (0.384) >0.05, the odd ratio (OR) value = 0.734 means that the pregnancy distance of women who are at risk of having a risk of having a risk of experiencing the SC delivery process is 0.734 times.